Composition of the essential oil of Cistus parviflorus L. from Turkey - (:unkn) unknown (ALLURED PUBL CORP, 2004)
ater distilled essential oil of Cistus parviflorus L. from Turkey was analyzed by GC/MS. Seventy-six representing 89.4% of the oil were identified. 8-alpha-13-oxy-14-ene-epilabdane (18.2%), manoyl oxide (9.1%) and delta-cadinene (6%) were characterized as major constituents.
Keywords: Cistus parviflorus; Cistaceae; essential oil composition; 8-alpha-13-oxy-14-ene-epilabdane; manoyl oxide; LAURIFOLIUS; LABDANE